A Comparison of the Structural Changes and IgG Immunobinding Activity of Parvalbumin in Salangid Icefish (Neosalanx taihuensis) After Glycation and Ultra-High Pressure Treatment - Ying Huang; Yang Hu; Jiawei Liu; Haiying Liu (Foods, 2025)
The aim of this study was to compare the effects of glycation and ultra-high pressure (UHP) treatment on the structure and IgG immunobinding activity of Salangidae icefish PV. The Circular Dichroism (CD) and Fluorescence Spectroscopy (FS) findings indicated that the glycation significantly affected both the secondary and tertiary structures of PV. However, the impact of UHP processing on the structure of PV was found to be less significant compared to the glycation. Western Blot analysis also revealed that the glycation markedly reduced the antigen specificity of PV. Conversely, UHP treatments at 300 MPa and 400 MPa slightly decreased the antigen specificity, whereas lower or excessively high pressures did not have a substantial impact. This research contributes valuable insights into strategies for reducing the allergenic potential of Salangid icefish.